Disaster education: empowering resilience and mitigating PTSD in disaster-prone areas of China - Xiaoshan Hu; Peisen Huang; Yang Lv; Mingxia Liu (Environmental Research Communications, 2023)
The people of disaster-affected communities are suffering from post-traumatic stress disorder (PTSD) due to the adverse effects of natural disasters. Education about disasters has become a possible strategy for fostering resilience and easing PTSD symptoms. This study intends to investigate the moderating roles of social support and disaster experiences on the relationships between disaster education, psychological resilience, and PTSD in disaster-prone regions of Southwest China. This study used Disaster Education Evaluation Scale, Psychological Resilience Scale (CD-RISC), Social Support Rating Scale (SRSS), event intensity Scale and Post Traumatic Stress Disorder Self-Rating Scale (PTSD-SS), surveyed 712 residents in Yunnan, Guizhou, Sichuan and other areas where natural disasters frequently occur in Southwest China. The research findings indicate that there is a negative association between disaster education and PTSD. The association is influenced by the presence of improved psychological resilience, which acts as a mediator. Additionally, it was discovered that disaster events positively moderated the relationship between psychological resilience and PTSD while social support negatively moderated it. Resilience has a noteworthy role as a substantial mediator, highlighting its crucial function in mitigating the detrimental consequences of catastrophes and amplifying the beneficial outcomes of disaster education. These results imply that building psychological resilience, which might reduce PTSD symptoms in people living in disaster-prone regions, is a critical part of disaster education. The strength of the catastrophic event and social support are other factors that affect how psychological resilience and PTSD are related. The research argues that disaster education is crucial for strengthening community resilience and reducing PTSD symptoms in at-risk areas. To increase psychological resilience and lessen PTSD in high-risk locations, policymakers and disaster management organizations should emphasize disaster education initiatives and strengthen social support network.